2020
DOI: 10.1029/2020sw002532
|View full text |Cite
|
Sign up to set email alerts
|

Medium Energy Electron Flux in Earth's Outer Radiation Belt (MERLIN): A Machine Learning Model

Abstract: The radiation belts of the Earth, filled with energetic electrons, comprise complex and dynamic systems that pose a significant threat to satellite operation. While various models of electron flux both for low and relativistic energies have been developed, the behavior of medium energy (120-600 keV) electrons, especially in the MEO region, remains poorly quantified. At these energies, electrons are driven by both convective and diffusive transport, and their prediction usually requires sophisticated 4D modelin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 84 publications
(138 reference statements)
2
39
0
Order By: Relevance
“…Another metric evaluated for the conjunction analysis is the correlation between the data sets. It has been demonstrated that the linear Pearson correlation can be affected by data noise, whereas the Spearman rank correlation is a more robust metric in the presence of outliers (e.g., Smirnov et al., 2020). The value of the Spearman correlation for GRACE‐COSMIC comparison is high (0.96), also illustrating that the two data sets closely agree with each other.…”
Section: Resultsmentioning
confidence: 99%
“…Another metric evaluated for the conjunction analysis is the correlation between the data sets. It has been demonstrated that the linear Pearson correlation can be affected by data noise, whereas the Spearman rank correlation is a more robust metric in the presence of outliers (e.g., Smirnov et al., 2020). The value of the Spearman correlation for GRACE‐COSMIC comparison is high (0.96), also illustrating that the two data sets closely agree with each other.…”
Section: Resultsmentioning
confidence: 99%
“…The combined data set thus covers more than two solar cycles. It can be useful for the long-term statistical analysis of electron flux behavior in the outer radiation belt, and can be incorporated into the empirical models of the medium energy electron flux, for example, by Smirnov, Berrendorf, et al (2020). Moreover, the electron fluxes converted to PSD can be used to set up boundary conditions for radiation belts modeling, as well as for data assimilation purposes.…”
Section: Discussionmentioning
confidence: 99%
“…The public data product (Morley et al, 2017) provides differential omnidirectional flux values at 15 energies from 120 keV up to 10 MeV, which we use in this study. For more information, including fit quality checks, see Smirnov et al (2020) and references therein.…”
Section: Instrumentationmentioning
confidence: 99%